2014
DOI: 10.3727/152599514x14143427352193
|View full text |Cite
|
Sign up to set email alerts
|

Surfing the Fringe: An Examination of Event Tourism Strategies of the Bleach Festival—Coolangatta Queensland

Abstract: Created as a celebration of art, music, and surf culture, the Bleach Festival was designed as a fringe-style event to be positioned in the week between two major surf events (Quiksilver/Roxy Pro and Burleigh Pro) held annually in Coolangatta, Queensland, Australia. Using visitor data collected at the event, in conjunction with an in-depth interview of the event's manager, the study evaluates the success of the festival against its own objectives of tourism extension, destination brand development, and local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Descriptive statistics such as frequencies and means were the most popular method [96.7% (current), 94.2% (initial), p = 0.400] for both reviews. However, unlike Tkaczynski and Rundle-Thiele's (2011) earlier research that identified a high number of studies (15.8%) employing descriptive statistics as the sole analysis method, only one study in the current review (Mackellar, 2014) exhibited this trait. Potentially due to the usage of data analysis techniques in PASW, the number of segmentation studies employing factor analysis [56.7% (current), 38.3% (initial), p = 0.008], analysis of variance [45.6% (current), 31.7% (initial), p = 0.040], and cluster analysis [27.8% (current), 11.7% (initial), p = 0.004] have risen in the past 7 years.…”
Section: Introductioncontrasting
confidence: 61%
“…Descriptive statistics such as frequencies and means were the most popular method [96.7% (current), 94.2% (initial), p = 0.400] for both reviews. However, unlike Tkaczynski and Rundle-Thiele's (2011) earlier research that identified a high number of studies (15.8%) employing descriptive statistics as the sole analysis method, only one study in the current review (Mackellar, 2014) exhibited this trait. Potentially due to the usage of data analysis techniques in PASW, the number of segmentation studies employing factor analysis [56.7% (current), 38.3% (initial), p = 0.008], analysis of variance [45.6% (current), 31.7% (initial), p = 0.040], and cluster analysis [27.8% (current), 11.7% (initial), p = 0.004] have risen in the past 7 years.…”
Section: Introductioncontrasting
confidence: 61%
“…Edinburgh thus, in marketing itself as a creative and cultural hub, provides a focus for businesses to work together toward developing festivals in the city. The portfolio is supported by government at all levels and by tourism business development groups (Mackellar, 2014). The basis of the portfolio is an adequate venue infrastructure, facilitating the staging of major and smaller community events in the yearround programming of the portfolio.…”
Section: Formalized Event Portfolios In Citiesmentioning
confidence: 99%
“…The use of festivals and events for explicit event tourism goals may aim at, for example, attracting tourists off-season, dispersing economic benefits derived from tourism, marketing and branding of the destination, using events as a catalyst for urban (re-)development and animating specific areas or attractions (e.g. Allen et al, 2011;Connell et al, 2015;Getz, 1991;2005;Getz and Page, 2016a;Hall, 1992;Mackellar, 2014;Mariani and Giorgio, 2017). All of these outcomes are embedded in the underlying key propositions presented by Getz and Page (2016a), mentioned in the introduction of this paper.…”
Section: Event Tourismmentioning
confidence: 99%
“…In an image-saturated society and in a competitive globalised world, where effective destination brands are becoming increasingly important, events can be used for destination promotion as well as the construction of a destination brand (e.g. Dinnie, 2011;Mackellar, 2014;Mendes et al, 2011). The widespread use of events for tourism-related outcomes such as the above has given rise to the study and strategic implementation of event tourism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation